Adult liver transplantation in the congenital absence of inferior vena cava. (October 2015) - Angelico, R.; Stonelake, S.; Perera, D.S.; Mirza, D.F.; Russell, S.; Muiesan, P.; Perera, M.T.P.R.
Abstract: Whereas congenital absence of inferior vena cava observed in paediatric population more often than not, as an isolated or syndromic variety, this is seldom encountered in adult liver transplant recipients. There appear few sporadic reports in the literature on experience of such anomaly in adults. Given the rarity of situation, surprising encounters of such anomalies may pose challenge to the unprepared transplant surgeon and unfavourable outcomes may even have resulted in under-reportage of this condition. In this brief report we document our recent experience with two such cases and this is supplemented with extensive reference to the literature on classification of such anomalies with the endeavour to document implications of such in the adult liver transplant setting. Highlights: Congenital absence of the infrahepatic inferior vena cava (IVC) amongst adult liver transplant recipients is rare. Radiological identification of vascular anomalies by routine pre-transplant imaging (CT/MRI) during transplant assessment work up is essential to plan appropriate strategies. Preservation of adequate length of native hepatic veins as they join the right atrium allows satisfactory outflow reconstruction with classic piggyback technique.